Sanksi Pidana bagi Pelaku Nikah Siri dalam Perspektif Hukum Islam - Saifudin Zuhri (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2014)
Through the Ministry of Religion, the government has drafted the legislation of law in the Religion Courts Subject about Marriage that discusses about unregistered marriages, polygamy, and marriage contract (mutah) as a complement of the Law No. 1/74 on Marriage. In the Article 143 of the draft mentioned the punishment for unregistered marriage, punished with a maximum fine of 6 million or imprisonment up to 6 months. The result of unregistered marriage inferential as follows: 1) there are legal and illegal unregistered marriage. It was to be plural or usual in society because a numbers of factor. 2) The assumption that seeing it as illegal and did not has a force of law looking for argumentation (istidlal) using qiyas method for equating record of ilan and wedding party, getting bennefit and li saddi az-zariah. 3) Criminalizing perpetrators of unregistered marriages through the provision of a prison sentence does not need to include Article 143 and Article 151, because marriage records violation is not a criminal act, only an administrative violation. 4) The actors of unregistered marriages can be punished a criminal fine in order to provide teaching and education. 5) Looking for argumentation using qiyas method on the ilan and wedding party are not relevan, because ilan and wedding party are sunnah. Even less the reason of consequence still an assumsion and does not muktabarak. On that account, would be not appropriate if the registration of marriages entered one of the pillars of marriage. 6) Sollution of the unregistered marriage case fine polygamy or monogamoy is marriage itsbat which there should be no provision prison sentence.